PELATIHAN PENGEMBANGAN PRODUK DAN PENGOLAHAN PASCA PANEN BIJI KOPI SINGLE ORIGIN BAGI KELOMPOK TANI DESA KUCUR, KABUPATEN MALANG - Wibowo, Wahyudi; Budianta, Tarsisius Dwi Wibawa; Suseno, Thomas Indarto Putut; Kristyanto, Visi Saujaningati; Skalastika, Brigita Rambu; Andriani, Angelica; Andreas, Stefanie Lorily; Banua, Agnes Caroline; Juanda, Keiko Zefanya (Jurnal Abdi Insani, 2024)
Malang Regency is known as one of the coffee agro-industry centers in East Java, where most of the coffee bean production in this area is produced by small-scale farmers. One of them is a coffee farmer community in the Kucur Village who belongs to the Republik Tani Mandiri (RTM) farmer group. The farmers' lands in Kucur Village are located on the slopes of Mount Kawi, at an altitude of 850-1,000 mdpl. The climate and fertile soil conditions in the area meet the requirements for coffee cultivation, especially for the Arabica type. The challenge of coffee development in Kucur Village lies in the fact that the produced coffee beans product (green beans) has not yet met high quality standards, necessitating the improvement of post-harvest processing techniques or further processing the beans into ground coffee to achieve a higher added value. This community service program aims to provide training and mentoring on standard post-harvest coffee bean processing techniques. The program was conducted in a participatory manner, beginning with the alignment of common goals and expectations with our farmer group counterpart. Then we continued with training on sorting, fermentation, drying, and storage techniques, which includes practical exercises. The farmer group counterparts' processing unit serves as the location for the training. The next stage is to provide assistance and evaluate the results of the training through testing the quality and taste of the Arabica coffee beans produced. There were four samples tested, each representing a different processing technique. Based on the results of the coffee bean quality test, all samples were met the criteria of Grade 1, or premium beans. Meanwhile, the cupping test results showed that all samples are scored above 80 points, indicating their classification as specialty coffee. These results suggest that the coffee beans has the potential to be developed as single origin coffee products, in the effort to enhance the economic value and welfare of the RTM coffee farmers.